Safety and immunogenicity of different doses and schedules of a live attenuated tetravalent dengue vaccine (TDV) in healthy adults: A Phase 1b randomized study. Issue 46 (17th November 2015) - Rupp, Richard; Luckasen, Gary Joseph; Kirstein, Judith Lee; Osorio, Jorge E.; Santangelo, Joseph D.; Raanan, Marsha; Smith, Mary Kathryn; Wallace, Derek; Gordon, Gilad S.; Stinchcomb, Dan T.
Highlights: A tetravalent dengue vaccine (TDV) was evaluated in a Phase 1b clinical trial. The different dose schedules and formulations of TDV were well tolerated. Greater that 80% of subjects seroconverted to three or more dengue viruses. Dosing twice on one day or reducing the dose had little effect on immunogenicity. These dose ranging studies help inform future Phase 2 and Phase 3 trials of TDV. Abstract: Introduction: A safe, effective dengue vaccine that can simultaneously induce immunity to all four dengue virus serotypes (DENV-1–4) is a public health priority. A chimeric tetravalent dengue vaccine (TDV) based on an attenuated DENV-2 serotype backbone was evaluated in healthy, flavivirus-seronegative adults. Methods: In this randomized, multicenter, Phase 1b study conducted in the United States, the safety and immunogenicity of TDV were evaluated in 140 participants aged 18–45 years in six dosing regimen study groups. Participants were injected subcutaneously on Days 0 and 90; placebo (saline) was injected where appropriate to maintain double blinding. Three different TDV dosages (TDV, a vaccine in which TDV-4 had been increased three-fold, and a one-tenth TDV dose), and single or double dosing were evaluated in one and/or both arms. Primary endpoints were solicited and unsolicited adverse events (AEs) and seroconversion rates to DENV-1–4 at Day 120. Results: The severity of all AEs was generally mild. The most common unsolicited AEs were headache (52%), fatigue (43%) and myalgia (29%). The incidence of injection site pain ranged from 29 to 64% and 5 to 52% among study groups after the first and second doses, respectively. At Day 120, the ranges of seroconversion rates among the groups were DEN-1: 84–100%; DEN-2: 96–100%; DEN-3: 83–100%; and DEN-4: 33–77%. More than 80% of participants in each group seroconverted to at least three dengue serotypes. Substantial GMT increases from baseline were observed for DEN-1–3 at all time points from Day 30 onward; DEN-4 GMT increases were lower. Increasing TDV-4 slightly increased DEN-4 GMT, did not impact DEN-2 and DEN-3 GMT, but reduced DEN-1 GMT. Neither multiple dosing in both arms, nor one-tenth TDV dosing meaningfully impacted GMT increases relative to TDV. Conclusions: All TDV doses and dosing schedules were well tolerated and immunogenic in healthy flavivirus-naive adults (ClinicalTrials.govNCT01511250 ).